A new species of seagrass-boring Limnoria (Limnoriidae, Isopoda, Crustacea) from Japan - Yoshino, Hiroki; Watabe, Hikari; Ohsawa, Takeshi A. (Zootaxa, 2017)
The marine seagrass-boring isopod, Limnoria rhombipunctata sp. nov. (Limnoriidae) is described from the rhizome of Phyllospadix iwatensis seagrass, in shallow coastal waters off Chiba Prefecture, Japan. L. rhombipunctata sp. nov. is distinguished from other Limnoria species by the unique carinae of pleonite 5 and pleotelson, two branched lacinia mobilis of the right mandible, 3 flagellar articles of antenna 1, and triangular epipod of the maxilliped. Specimens of L. magadanensis, a species similar to L. rhombipunctata sp. nov., are re-examined and compared with L. rhombipunctata sp. nov.